2016
DOI: 10.3847/0004-637x/832/1/47
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Possible Quasi-Periodic Oscillations in the Long-Term Optical Light Curve of the Bl Lac Object Oj 287

Abstract: Detection of periodicity in the broad-band non-thermal emission of blazars has so far been proven to be elusive. However, there are a number of scenarios which could lead to quasi-periodic variations in blazar light curves. For example, orbital or thermal/viscous period of accreting matter around central supermassive black holes could, in principle, be imprinted in the multi-wavelength emission of small-scale blazar jets, carrying as such crucial information about plasma conditions within the jet launching reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 59 publications
(62 reference statements)
5
118
0
Order By: Relevance
“…The cases of OJ 287, 3C279, PKS 1510-089, PKS 2005-489 have also been studied. We note that in the optical for OJ 287 there is rather robust evidence of a 12-year oscillation (Sillanpää et al 1988;Lehto & Valtonen 1996), while low-significant quasi-periodities T γ ∼ T opt ∼ 400 d (Sandrinelli et al 2016a) have recently been confirmed in optical by Bhatta et al (2016), who also found a harmonically connected peak at T opt ∼800 days.…”
Section: Introductionmentioning
confidence: 79%
“…The cases of OJ 287, 3C279, PKS 1510-089, PKS 2005-489 have also been studied. We note that in the optical for OJ 287 there is rather robust evidence of a 12-year oscillation (Sillanpää et al 1988;Lehto & Valtonen 1996), while low-significant quasi-periodities T γ ∼ T opt ∼ 400 d (Sandrinelli et al 2016a) have recently been confirmed in optical by Bhatta et al (2016), who also found a harmonically connected peak at T opt ∼800 days.…”
Section: Introductionmentioning
confidence: 79%
“…The source brightness in magnitudes was converted into the flux in mJy units by using the zero points for the Johnson-Cousins UBVRI photometric system as given in Table A2 of [43], and to calculate the optical spectra the fluxes were interstellar-extinction corrected using the extinction magnitudes for various filters listed in the NED. 3 …”
Section: Observations and Data Processingmentioning
confidence: 99%
“…One of the most important properties that characterize blazars is their variability over a broad range of temporal and spatial frequencies. The variability in general is found to be aperiodic in nature; however, recently, detection of quasi-periodic oscillations in various emission frequencies and timescales have been reported (see [2][3][4]). In particular, low amplitude, rapid variability in the timescales less than a day is widely known as intraday/intranight or microvariability.…”
Section: Introductionmentioning
confidence: 99%
“…The method, like the LSP, also attempts to fit sinusoidal waves to the data; however the waves can be localized in both time and frequency domains to account for the transient nature of QPOs (Bravo et al 2014;Torrence & Compo 1998). The method has been widely used in the time series analysis of blazar light curves(e.g., Bhatta et al 2016c;Mohan & Mangalam 2015;Bhatta et al 2013;Hovatta et al 2008). To look for the possible QPOs in the radio light curve of the blazar PKS 0219-164, we employed weighted wavelet z-transform (WWZ), a method described in Foster (1996).…”
Section: Radio and γ-Ray Variabilitymentioning
confidence: 99%